2004
DOI: 10.1577/02-139
|View full text |Cite
|
Sign up to set email alerts
|

Variable Effects of Habitat Enhancement Structures across Species and Habitats in Michigan Reservoirs

Abstract: Abstract.-The addition of habitat enhancement structures to aquatic systems is a common practice by fisheries managers hoping to increase production, spawning success, and angler catch rates of important sport fishes. However, quantitative evaluations of these efforts are few and typically do not include the extent to which natural habitat mediates the effects of habitat enhancement structures. We evaluated the effects of two types of habitat enhancement structure on four fish groups in four reservoirs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
(39 reference statements)
2
41
0
Order By: Relevance
“…The strength of this effect depends on the species of fish and the amount of structure available in the surrounding area (Bolding et al 2004;Wills et al 2004). There is an active debate about whether such artificial structures actually increase population size, or merely attract fish from other areas.…”
Section: Physical Complexitymentioning
confidence: 99%
“…The strength of this effect depends on the species of fish and the amount of structure available in the surrounding area (Bolding et al 2004;Wills et al 2004). There is an active debate about whether such artificial structures actually increase population size, or merely attract fish from other areas.…”
Section: Physical Complexitymentioning
confidence: 99%
“…Our experimental reefs were separated from each other by a distance of at least 30 m. Previous experiments with freshwater reefs have used similar distances between replicates, ranging from 3 to 100 m (median ¼ 40 m) (Wilbur 1978, Walters et al 1991, Hayse and Wissing 1996, Rold et al 1996, Samdstro¨m and Karas 2002, Wills et al 2004, Freitas et al 2005, Santos et al 2008. We are confident that our results are not severely affected by confusion with spatial variation or spatial dependence because: (1) the three material types were spatially interspersed (Fig.…”
Section: Data Analysesmentioning
confidence: 79%
“…Community change rates indicated that although ceramic reefs were more promptly colonized, concrete reefs benefited from a secondary increase in species gain rates, following the initial decrease which is general of most successions (Anderson 2007). We believe that these differences are not due to confounding environmental variables or the physical complexity and size of the reefs, which have been shown to affect the availability of predation refuges, food, or spawning substrata (Walters et al 1991, Rold et al 1996, Bolding et al 2004, Wills et al 2004), because we carefully matched the dimensions and complexity of the reefs, and we placed the reefs in an environmentally homogeneous area, with no detectable differences in physicochemical features among sites. Although further data are needed to understand the mechanisms generating these differences among materials, ceramic and concrete were more promptly and intensively colonized by periphyton than the PVC treatments (L. N. Santos, personal observation), which also had a different species composition.…”
Section: Species Composition and Reef Materialsmentioning
confidence: 88%
See 2 more Smart Citations